The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/om400651p
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic C–H Borylation and Related Reactions of B–H Boron Cations

Abstract: Catalytic procedures are described for aminedirected borylation of aliphatic and aromatic tertiary amine boranes. Sequential double borylation is observed in cases where two or more C–H bonds are available that allow 5-center or 6-center intramolecular borylation. The HNTf2 catalyzed borylation of benzylamine boranes provides a practical means for the synthesis of ortho-substituted arylboronic acid derivatives, suitable for Suzuki-Miyaura cross-coupling applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 26 publications
(50 reference statements)
3
54
0
Order By: Relevance
“…Catalytic (in activators such as HNTf 2 ) variants using borenium equivalents were concurrently developed ( Fig. 10) [7,49]. The key step in the catalytic cycle involves hydride transfer from (amine)BH 3 to 15 to regenerate 13 (or its functional equivalent).…”
Section: Intramolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalytic (in activators such as HNTf 2 ) variants using borenium equivalents were concurrently developed ( Fig. 10) [7,49]. The key step in the catalytic cycle involves hydride transfer from (amine)BH 3 to 15 to regenerate 13 (or its functional equivalent).…”
Section: Intramolecular Electrophilic Aromatic Borylationmentioning
confidence: 99%
“…Thus Vedejs and co-workers demonstrated that intramolecular aliphatic C-H borylation using highly electrophilic [(R 3 N)BH 2 ] + borenium cations, or their equivalents, was also possible. Activation of amine borane 19 with [Ph 3 C][B (C 6 F 5 ) 4 ] led to the evolution of H 2 and formation of the spiro borenium cation 20 (which was subsequently characterised by X-ray diffraction studies) [49,57]. A C-H insertion mechanism was proposed proceeding via a four-membered transition state.…”
Section: Intramolecular Electrophilic Aliphatic Borylationmentioning
confidence: 99%
See 1 more Smart Citation
“…A stepwise hydride abstraction of the borane complexes is identified. 56 For example, the addition of 0.5 equivalent of trityl salt to the NHC-BH 3 complex (19) [13] 2+ .…”
Section: Polynuclear Boron Dicationsmentioning
confidence: 99%
“…6 Borocations, which feature a cationic boron centre and thus act as boron electrophiles, are traditionally classified by their coordination number: two-coordinate boriniums, three-coordinate boreniums, and four-coordinate boroniums. Due to the fact that boriniums are often highly unstable, thereby requiring extensive steric or electronic stabilisation, 7 and boroniums often possess low Lewis acidity as a result of the saturated coordination sphere at boron, boreniums represent an attractive target of investigation, occupying a middle ground between stability and reactivity (Lewis acidity).…”
mentioning
confidence: 99%